Roles of Hepatic Innate and Innate-Like Lymphocytes in Nonalcoholic Steatohepatitis - Chen, Yongyan; Tian, Zhigang (Frontiers in Immunology, 2020)
Nonalcoholic steatohepatitis (NASH), a progressive form of nonalcoholic fatty liver disease (NAFLD), is accompanied by steatosis, hepatocyte injury and liver inflammation, which has been a health problem in the world as one of the major high risk factors of cirrhosis and hepatocellular carcinoma (HCC). Complex immune responses involving T cells, B cells, Kupffer cells, monocytes, neutrophils, DCs and other innate lymphocytes account for the pathogenesis of NASH; however, the underlying mechanisms have not been clearly elucidated in detail. In the liver, innate and innate-like lymphocytes account for more than two-thirds of total lymphocytes and play an important role in maintaining the immune homeostasis. Therefore, their roles in the progression of NASH deserves investigation. In this review, we summarized murine NASH models for immunological studies, including the diet-induced NASH, chemical-induced NASH and genetic-induced NASH. The role of innate and innate-like lymphocytes including NK cells, ILCs, NKT, γδT and MAIT cells in the progression of NASH were elucidated. Further, the metabolic regulation of the innate immune response was addressed in consideration to explain the molecular mechanisms. Based on the findings of the reviewed studies, strategies of immune intervention are proposed to control the progression of NASH.